2005
DOI: 10.1359/jbmr.041231
|View full text |Cite
|
Sign up to set email alerts
|

Population Trends in BMD Testing, Treatment, and Hip and Wrist Fracture Rates: Are the Hip Fracture Projections Wrong?

Abstract: A worldwide epidemic of hip fractures has been predicted. Time trends in BMD testing, bone-sparing medications and hip and wrist fractures in the province of Ontario, Canada, were examined. From 1996 to 2001, BMD testing and use of bone-sparing medications increased each year, whereas despite the aging of the population, wrist and hip fracture rates decreased.Introduction: If patients with osteoporosis are being diagnosed and effective treatments used with increasing frequency in the population, rates of hip a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
133
2
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(161 citation statements)
references
References 50 publications
18
133
2
8
Order By: Relevance
“…Our observed temporal trends are consistent with previous studies [13,14,33]. A Canadian study [13] In a similar American study [33], age-adjusted hip fracture rates fell by 20 % between 1993 and 2003; however, in the cohort 75 years and older, age-adjusted rates fell by 4.0 % in women but increased by 6.8 % in men.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our observed temporal trends are consistent with previous studies [13,14,33]. A Canadian study [13] In a similar American study [33], age-adjusted hip fracture rates fell by 20 % between 1993 and 2003; however, in the cohort 75 years and older, age-adjusted rates fell by 4.0 % in women but increased by 6.8 % in men.…”
Section: Discussionsupporting
confidence: 91%
“…A Canadian study [13] In a similar American study [33], age-adjusted hip fracture rates fell by 20 % between 1993 and 2003; however, in the cohort 75 years and older, age-adjusted rates fell by 4.0 % in women but increased by 6.8 % in men. An Ontario study spanning 1992 to 2000 [14] observed a decline in hip and wrist fracture rates beginning in 1997, correlating with an increase in bone mass density (BMD) testing and osteoporosis medications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A typical patient with a hip fracture spends US $40 000 in the first year following hip fracture for direct medical costs and almost $5000 in subsequent years. 1,[18][19][20] Despite recent literature indicating that the hip fracture incidence may be stabilizing or decreasing, [21][22][23][24][25][26][27][28][29] concern still exists that because of the aging of the population, the hip fracture incidence will increase worldwide unless additional steps are taken. 7,19,20,22,[30][31][32][33][34][35] Understanding the incidence and postsurgical outcome of hip fractures is a vital first step in improving population health.…”
mentioning
confidence: 99%